Interleukin 15 is produced by endothelial cells and increases the transendothelial migration of T cells In vitro and in the SCID mouse-human rheumatoid arthritis model In vivo. - Oppenheimer-Marks, N (1998)
The capacity of endothelial cells (EC) to produce IL-15 and the capacity of IL-15 to influence transendothelial migration of T cells was examined. Human umbilical vein endothelial cells expressed both IL-15 mRNA and protein. Moreover, endothelial-derived IL-15 enhanced transendothelial migration of T cells as evidenced by the inhibition of this process by blocking monoclonal antibodies to IL-15. IL-15 enhanced transendothelial migration of T cells by activating the binding capacity of the integrin adhesion molecule LFA-1 (CD11a/CD18) and also increased T cell motility. In addition, IL-15 induced expression of the early activation molecule CD69. The importance of IL-15 in regulating migration of T cells in vivo was documented by its capacity to enhance accumulation of adoptively transferred human T cells in rheumatoid arthritis synovial tissue engrafted into immune deficient SCID mice. These results demonstrate that EC produce IL-15 and imply that endothelial IL-15 plays a critical role in stimulation of T cells to extravasate into inflammatory tissue.